2018
DOI: 10.1186/s12955-018-0929-4
|View full text |Cite
|
Sign up to set email alerts
|

Consistency of health-related quality of life among people living with HIV: Latent state-trait analysis

Abstract: BackgroundThe aim of this longitudinal study was to examine the consistency of health-related quality of life (HRQoL) among people living with HIV (PLWH) by breaking down the variance of repeated HRQoL measures into trait, state, and method components and to test the stability of HRQoL over time. In addition, we wanted to examine whether HRQoL trait components are related to personality traits, while controlling for selected socio-medical variables.MethodsThree assessments were performed with a six-month lag o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 76 publications
0
4
0
Order By: Relevance
“…Prevention of TB-IRIS has clear physical benefits which in the short period of time may not directly translate into perceived improvements in psychosocial aspects of HRQoL. ‘Stigma’, ‘social relationships’ or ‘emotional distress’ can be considered distal constructs requiring structural or psychosocial changes to improve over time, which are not directly attributable to medical interventions ( Rzeszutek and Gruszczyńska, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Prevention of TB-IRIS has clear physical benefits which in the short period of time may not directly translate into perceived improvements in psychosocial aspects of HRQoL. ‘Stigma’, ‘social relationships’ or ‘emotional distress’ can be considered distal constructs requiring structural or psychosocial changes to improve over time, which are not directly attributable to medical interventions ( Rzeszutek and Gruszczyńska, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, an international randomized trial discovered immediate treatment could significantly improve self-assessed quality of life (QoL) in healthy PLWH [1]. Another longitudinal study indicated QoL among PLWH had uniqueness in a clinical practice [2]. Nevertheless, current literature was scarce on studies that analyzed the relationship between treatment activities and adaptive adjustment among PLWH.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, openness was associated with better global cognitive function in HIV [ 20 ]. Furthermore, in patients living with HIV, higher neuroticism and lower extraversion were associated with poorer quality of life, and lower conscientiousness was linked to depression [ 21 , 22 , 23 ]. In patients with hepatitis C virus taking pegylated interferon and ribavirin, low self-directedness was associated with induced depression by the antiviral drugs [ 24 ].…”
Section: Introductionmentioning
confidence: 99%